Carlos E. Alchourrón. Breve biografía intelectual - Gladys Palau (Crítica)
This paper is a short intellectual biography of Professor Carlos E. Alchourrón. I analyze his main contributions in three fields: 1) the logic of normative systems, 2) the logic of theory change, and 3) the logic of defeasible conditionals. I review the historical development of his thought on these three subjects. Furthermore, I show how the problems that arise in the field of normative logic stimulated him to find solutions in the AGM theory and in defeasible logic. Lastly, I show how in his last papers these three fields converge in a general englobing approach.